Saccharomyces cerevisiae-Based Probiotics as Novel Antimicrobial Agents to Prevent and Treat Vaginal Infections - Gaziano, Roberta; Sabbatini, Samuele; Roselletti, Elena; Perito, Stefano; Monari, Claudia (Frontiers in Microbiology, 2020)
Vaginal infections affect 70% of women during their lifetimes and accounts for millions of annual doctors’ visits. These infections are predominantly represented by vulvovaginal candidiasis (VVC) and bacterial vaginosis (BV). Although standard antimicrobial agents remain the major strategy for the prevention and treatment of vaginal infections, both VVC and BV are difficult to treat due to high rates of resistance and recurrence, high probability of complications, and negative effects on the vaginal microbiota. This review focuses on a new approach of yeast-based probiotics for the prevention and/or treatment of these common vaginal infections.